Imperfect strangers: Picturing place, family, and migrant identity on Facebook. (March 2015) - Aguirre, Alwin C.; Davies, Sharyn Graham
Abstract: Places have meanings and significances beyond mere location or functionality. This assertion becomes especially salient for migrants, whose status is defined by a physical move from one place to another. The aim of this paper is to discuss the practice of place-making by migrants, with specific focus on the role of Facebook in this endeavour. We present the particular case of Amy, a Filipina immigrant to New Zealand, and her Facebook activities. Central to the discussion is a four-minute audio-visual piece that she produced herself and posted online to commemorate her family's second year as New Zealanders. Guided by the framework of multimodality, the concept of place, and the practice of everyday photography, and with invaluable insights from a semi-structured interview of the participant, we illustrate how semiotic resources afforded by social media sites such as Facebook foster the construction of the discourse of the good life and a claim to national belonging. Our analysis shows that everyday family photography, in interaction with social media, potentially signifies migrants' becoming a natural part of the national landscape. By interrogating the boundaries of private and public spaces, and reproducing the "migrant gaze" in everyday family photography, Amy transforms images into unified strands of the ideal immigrant narrative. Highlights: The digital era emboldens acts of self-presentation as signifying projects. Facebook fosters the construction of the good life in migrant identity work. Multimodal resources articulate and silence certain aspects of migrant reality. Facebook family photography potentially signifies migrants' national belonging. The migrant gaze transforms everyday images to narratives of place and ideal life.